Ekonomi Rumah Tangga Petani : Pola Pertanian Terpadu di Propinsi Riau (Household Economic Farmers: integrated farming in the province of Riau) - Latifa Siswati (Jurnal Embrio, 2012)
This study aims to: 1) Identify the behavior of production, consumption and application of integrated farming technology in households that implement the integration of plantations, crops and cattle in the province of Riau. 2) Provided the identification of resilience and response capacity of households to maintain the sustainability of integrated farming and household needs 3) Knowing the impact of external factors on the economic decisions of farmers farming households integrated farm, crops and cattle according to the farmers in the province of Riau. The model is formulated in this study is the structural equation model simultaneously. The model has 56 equations consisting of 32 structural equations and 24 identities equations. The number of endogenous variables as much as 56 and as many as 51 exogenous variables. Once the model is identified by using the order condition, obtained the whole equation is "overidentified" and the estimation method applied is the method of 2 SLS (Two Stage Least Squares). The results showed that farmers who apply the integration of food crops, plantation crops and cattle to create jobs for the community, increase production and incomes of farmers. In terms of preparedness, farmers may be prepared in the cattle business which can not be properly developed. To improve the welfare of farmers, the combination of product price increases, wage rates and non-farm income provides a better impact of increasing use of labor in both farm and non-agricultural business on, the outpouring of labor in the family business and the outpouring of labor in other business other, farm production and disposable income.